An analysis of the biomechanics of interference screw fixation and sheathed devices for biceps tenodesis. Issue 6 (July 2015) - Saithna, Adnan; Chizari, Mahmoud; Morris, Guy; Anley, Cameron; Wang, Bin; Snow, Martyn
Abstract: Background: This study aimed to evaluate the differences in biomechanical properties of biceps tenodesis when performed with sheathed versus unsheathed screws and also to investigate the effect of altering the pre-tension. Methods: Tenodesis was performed in an in vitro model using biomechanical test blocks and ovine tendons. Blocks were allocated to 1 of 5 groups which varied by method of tenodesis and cyclical loading protocol: Group A, Biosure PK screw (10–100 N), Group B: 7–8 mm Biosure Sync and Biosure PK screw (10–100 N), Group C: Biosure PK screw (10–70 N), Group D: Biosure PK (20–100 N), and Group E: custom sheath and Biosure PK screw (10–100 N). If tenodeses remained intact after 500 cycles maximum load to failure testing was performed. Findings: 30% of tenodeses in Group A failed prior to 500 cycles whereas none failed in the sheathed device groups ( P  = 0.02). Using a sheathed device prevented mal-rotation. However, tenodeses in Group B were more likely to fail immediately distal to the tenodesis at a load below the anticipated maximum load to failure suggesting tendon damage during fixation. Using the custom sheath, which did not have sharp edges, resulted in a statistically significant increased maximum load to failure in Group E (348 N) when compared to Group A (228 N, mean difference 120 N, P  = 0.01) and Group B (253 N, mean difference 95 N, P  = 0.0007). Interpretation: Sheathed devices prevent mal-rotation and increase stiffness and maximum load to failure. This is further improved by reducing tendon damage at the time of tenodesis. Highlights: Revision rates as high as 36–45% are reported for arthroscopic biceps tenodesis. Tendon injury and mal-rotation during screw insertion result in early failures. Using a sheathed device can reduce mal-rotation and increase the stiffness of tenodesis. Tendon damage can be minimised by using a sheath without sharp edges or splines.